Metabolomics insights into the protective molecular mechanism of Vaccinium myrtillus against oxidative stress in intestinal cells - Sara Novi; Vicky Caponigro; Maria Rosaria Miranda; Giovanna Aquino; Matteo Delli Carri; Emanuela Salviati; Silvia Franceschelli; Carla Sardo; Manuela Giovanna Basilicata; Vincenzo Vestuto; Mario Felice Tecce; Federico Marini; et al. (Scientific Reports)
Abstract Blueberry (Vaccinium myrtillus L.) is a rich source of secondary metabolites known for their potent antioxidant, anti-inflammatory, and cytoprotective properties. These compounds are essential in neutralizing reactive oxygen species (ROS), which are implicated in oxidative stress-related diseases. In this study, we induced oxidative stress in IEC-6 small intestine cells using hydrogen peroxide (H2O2), creating a cellular model to investigate the biochemical response. The obtained results showed that a blueberry extract (BLUBE) significantly exhibited strong antioxidant capacity, as evidenced by DPPH, FRAP and ABTS in vitro tests. Additionally, BLUBE effectively inhibited the release of reactive species in cells and enhanced cytoprotective response, as indicated by improved wound healing and clonogenic potential reduction of stress fibers rearrangement and apoptosis. Metabolomic analysis, specifically High-Resolution Mass Spectrometry (HR-MS), was employed to elucidate the metabolic alterations associated with the protective activity of BLUBE against oxidative stress in IEC-6 cells. Chemometric approaches were applied to preprocess the data, explore variability, and identify systematic biases, ensuring the removal of batch effects and other experimental artifacts. A Partial Least Squares Discriminant Analysis classification model confirmed clear group stratifications with high accuracy (98.75 ± 2.31%), sensitivity, and specificity, aiding in the identification of significant metabolites for pathway enrichment analysis. Key metabolic pathways, including sphingolipid metabolism, taurine and hypotaurine metabolism, glycerophospholipid metabolism, and cysteine and methionine metabolism, were significantly modulated, supporting the biochemical basis of BLUBE’s protective effects. In fact, BLUBE was able to partially reverse the downregulation of these pathways, effectively reducing oxidative stress and promoting cell survival. This study highlights the power of HR-MS-based metabolomics in uncovering the mechanisms of nutraceuticals and emphasizes the potential of BLUBE as a protective agent for oxidative stress-related diseases. It also underscores the growing significance of metabolomics in the food and pharmaceutical industries.